The Study Of Awareness Regarding Sex Education At SMK Khir Johari / Syazani Marzuki...[et al.] - Marzuki, Syazani; Zakaria, Nurul Zafirah; Wan Mohamad, Wan Sumayyah Syahidah; Omar, Siti Norfarhana (2010)
The title of this research is a study of awareness of sex education at SMK Khir Johari, Sg Petani, Kedah. Globalization and the rapid development of country is one of the factors which lead to the social changes. These changes can affect the moral, norms, perception as well as the human behavior in order to adopt the technological changes respectively. Nonetheless, the bad impact was affecting to our society especially to the teenagers. Younger becoming sexually active early then suppose to be. From this perspective. this article offers a conceptual framework on the study of awareness of sex education, the relationship between sex education in school (Abstinence and ccomprehensive method), parenting roles, peers pressure with awareness of sex education. Total respondents of 150 students from form 1 untul form 5 in SMK Khir Johari to fill the set of questionnairre that consist of saction which are demogrtaphic data (Section A), peer pressure (Section B), perenting role (Section C), abstinence (Section D), comprehensive (Section E) and awareness of sex education (Section F). This research used quantitative method. The research conducted by using chi square of statistical of package for social science SPSS version 16.0 and the data was analysed with the Pearson Correlation. The result indicated that there were positive correlation between parenting role and awareness of sex education, sex education program (abstinence and comprehensive method) and awareness of sex education. However, there has been found that to be no correlation between peers, pressure and awareness of sex education. It was designed to examine the purpose of the study, the types of investigation, the extent of researcher interference, the study setting, the unit of analysis, and the time horizon of the study that is essential to conduct the study of awareness regarding sex education.